P64 Self-harm among the homeless population in ireland: a national registry-based study of incidence and associated factors. (3rd September 2019) - Barrett, PM; Griffin, E; Corcoran, P; O'Mahony, MT; Arensman, E
Abstract : Background: Suicide rates are higher among the homeless population than the general population, and the homeless are recognised as a priority group for suicide prevention. Self-harm is a strong predictor of future suicide, particularly repetition of self-harm. Little is known about the incidence of self-harm, and its associated predictive factors, among the homeless. The purpose of this study was to quantify the burden of self-harm among the homeless population in Ireland, and to assess factors associated with self-harm and repeated self-harm. Methods: Data on self-harm presentations to all 34 hospital emergency departments in Ireland were collected by the National Self-Harm Registry Ireland (NSHRI). Index and repeat presentations from 2010–2014 were included for the homeless and fixed residence populations. Individuals with no fixed abode, or who lived in recognised accommodation for the homeless, were recorded as being homeless. Age-standardised incidence rates (ASIR) of self-harm were calculated using NSHRI data and national population estimates from the Census of Ireland. Factors associated with self-harm and repetition of self-harm were compared between the homeless and those living at fixed residence using multivariable-adjusted logistic regression models. Results: There were 58, 747 presentations of self-harm in total, of which 3.9% were among the homeless. The ASIR of self-harm was 30 times higher among the homeless (5, 572 presentations per 100, 000) compared with those living at fixed residence (187 presentations per 100, 000). Intentional overdose was the most common method of self-harm for all; relative to those with fixed residence, homeless individuals were significantly more likely to use minor tranquillisers (47% vs 39%, χ 2 :p<0.001) or street drugs (19% vs. 6%, χ 2 :p<0.001) for overdose. Homeless people had significantly higher odds of self-harm repetition within 12 months (vs. fixed residence, AOR 1.46, 95%CI 1.21–1.77). Within the homeless population, the odds of self-harm repetition were significantly increased among those who engaged in self-cutting (vs. overdose, AOR 1.76, 95%CI 1.17–2.65) and those who did not receive psychiatric review at index presentation (vs. reviewed, AOR 1.54, 95%CI 1.05–2.26). Conclusion: There is a disproportionate burden of self-harm among the homeless. Those who present with self-cutting, and who do not receive psychiatric review at index presentation, are particularly vulnerable to repetition. Although this study only reflects self-harm presenting to hospital, and assumes no change in homelessness status during follow-up, it is the largest study of self-harm among the homeless conducted to date. The results may be used to strengthen suicide prevention efforts through earlier recognition of high-risk homeless individuals.